Risk Management in the Digital Era for SMEs - Jangkhum, Sarunyar Jangkhum; Chayutrakorn, Chalita; Uthai, Prasong; Ratna Sari Supiyanti (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
Risk management is a critical component that enables small and medium-sized enterprises (SMEs) to adapt and sustain their operations in the digital era. This study explores the application of two internationally recognized frameworks, ISO 31000 and COSO ERM, to assist SMEs in managing risks systematically and effectively. The research adopts a documentary research methodology, analyzing and synthesizing risk management strategies tailored for SMEs. The findings indicate that ISO 31000 provides a high level of flexibility, making it particularly suitable for small SMEs that require a simple, immediately applicable approach. In contrast, COSO ERM is better suited for medium-sized SMEs seeking to integrate risk management into their organizational strategy to enhance competitiveness. Moreover, this study proposes a risk management model that combines both frameworks, aligning with the size and nature of SMEs in the digital context.